Optimizing Students' Speaking Skills: Arabic Language Learning Model Based on Bi'ah Lugawiyyah in Islamic Higher Education Institutions | Tahsin Maharat al-Kalam lada al-Tullab: Namudhaj Ta'allum al-Lughah al-'Arabiyyah al-Qa'im 'ala al-Bi'ah al-Lughawiyyah fi al-Jami'ah al-Islamiyyah - Takdir Takdir; Nur Agung; Amran AR (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
The teaching of Arabic in higher education has yet to fully utilize the language environment as a learning resource. However, improving Arabic speaking skills is closely linked to the language environment. This study aims to develop a valid, practical, and effective Arabic language learning model to enhance students' speaking skills at Islamic higher education institutions. This research employed a Research and Development (R&D) approach, utilizing the ADDIE model designed by Branch, which consists of five phases: analysis, design, development, implementation, and evaluation. The study involved 23 students for testing practicality and effectiveness, as well as two experts for validating the model. Data were collected through questionnaires, interviews, observation sheets, and speaking skill tests. Both qualitative and quantitative methods were used for data analysis. The findings indicate that the Arabic language learning model based on the bi